Coronary surgery is superior to drug eluting stents in multivessel disease. Systematic review and meta-analysis of contemporary randomized controlled trials. (1st May 2016) - Benedetto, Umberto; Gaudino, Mario; Ng, Colin; Biondi-Zoccai, Giuseppe; D'Ascenzo, Fabrizio; Frati, Giacomo; Girardi, Leonard N.; Angelini, Gianni D.; Taggart, David P.
Abstract: Objective: Current randomized controlled trials (RCTs) comparing percutaneous coronary intervention with drug eluting stent (DES-PCI) with coronary artery bypass grafting (CABG) in multivessel disease are underpowered to detect a difference in hard clinical end-points such as mortality, myocardial infarction and stroke. We aimed to overcome this limitation by conducting a meta-analysis of contemporary RCTs. Methods: A systematic literature search was conducted for all RCTs comparing DES-PCI versus CABG in multivessel disease published through May 2015. Inverse variance weighting was used to pool data from individual studies (< 1 favouring DES-PCI and > 1 CABG favouring surgery). Results: A total of five randomized trials including 4563 subjects were analysed. After an average follow-up of 3.4 years, DES-PCI was associated with a significantly increased risk of overall mortality (HR 1.51; 95%CI 1.23–1.84; P < 0.001), MI (HR 2.02; 95%CI 1.57–2.58; P < 0.001) and repeat revascularization (HR 2.54; 95%CI 2.07–3.11; P = < 0.001). CABG marginally increased the risk of stroke (HR 0.70; 95%CI 0.50–0.98; P = 0.04). The absolute risk reduction for all-cause mortality (3.3%) and myocardial infarction (4.3%) with CABG was larger than the absolute risk reduction for stroke (0.9%) with DES-PCI. Conclusion: In patients with multivessel coronary disease, CABG was found to be superior to DES-PCI by reducing the risk of mortality and subsequent myocardial infarction at the expense of a marginally increased risk of stroke.